(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The aim of this study was to ascertain yield and yield gap status of major crops. The study was conducted in two villages of sadar upazila under the Mymensingh district. Ninety farmers were selected as sample size following proportionate random sampling technique. The researcher himself personally collected data during mid-March to mid-May 2014. Collected data were compiled, coded, analyzed and interpreted as per objectives of the study. It was found that majority of the respondents were middle-aged having a primary level of education, medium farm size, small family size with low agricultural knowledge but the favorable attitude towards the current agricultural system. Boro rice, Mustard, Bitter gourd, and Black gram are the major crops of the study area. Yields of Boro rice, Mustard, Bitter gourd and black gram in farmers’ field were found 5,295 Kg/ha, 703 Kg/ha, 12,654 Kg/ha and 771 Kg/ha with mean yield gap of 704 Kg/ha, 396 Kg/ha, 9,345 Kg/ha and 628 Kg/ha, respectively. Farmers’ characteristics like age, farming experience, agricultural training, knowledge about agriculture and attitude towards agricultural practices found negatively related to their yield gap of the major crops. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (3), 174-181